Model Pengembangan Instrumen Penilaian HOTS dalam Keterampilan Menulis Teks Deskripsi Fase D (SMP Kelas VIII) - Tri Puji Setyawati; Kuntoro (CV Edujavare Publishing, 2026)
This research aimed to design and produce a Higher Order Thinking Skills (HOTS)-based assessment instrument for descriptive text writing skills for Phase D students (grade VIII of junior high school). This research was motivated by the need for authentic assessments that not only assess the final written product but also consider students' thinking processes, attitudes, and creativity during the writing process. The research and development method used included needs analysis, assessment instrument design, and conceptual validation. The instrument developed encompassed aspects of attitudes, knowledge, and skills, with a focus on higher-order cognitive abilities at levels C4 to C6. The results showed that the HOTS-based assessment instrument facilitated students' critical, reflective, and creative thinking in producing descriptive texts. Therefore, this instrument is expected to serve as an alternative assessment tool for teachers in conducting more meaningful learning evaluations that align with the learning outcomes of the Independent Curriculum.